2020
DOI: 10.1371/journal.pone.0227349
|View full text |Cite
|
Sign up to set email alerts
|

The ESAS-score: A histological severity grading system of subarachnoid hemorrhage using the modified double hemorrhage model in rats

Abstract: The amount of extravasated blood is an established surrogate marker for subarachnoid hemorrhage (SAH) severity, which varies in different experimental SAH (eSAH) models. A comprehensive eSAH grading system would allow a more reliable correlation of outcome parameters with SAH severity. The aim of this study was to define a severity score for eSAH related to the Fisher-Score in humans. Material and methods SAH was induced in 135 male rats using the modified double hemorrhage model. A sham group included 8 rats,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…Previous studies were able to demonstrate that this specific model facilitates the reliable induction of severe SAH with a high incidence of vasospasm, making it specifically suitable for the evaluation of this phenomenon. 17,18,31 In the present study, we found an overall high incidence of cerebral vasospasm on day 2 (65%) as well as on day 5 (86%), which again reflects the aforementioned benefits of this experimental SAH-model. Considering vasospasm severity, expectedly, severe vasospasm was seen more often on day 5 (49%) compared to day 2 (21%).…”
Section: Cerebral Vasospasm In Experimental Sah Modelssupporting
confidence: 79%
“…Previous studies were able to demonstrate that this specific model facilitates the reliable induction of severe SAH with a high incidence of vasospasm, making it specifically suitable for the evaluation of this phenomenon. 17,18,31 In the present study, we found an overall high incidence of cerebral vasospasm on day 2 (65%) as well as on day 5 (86%), which again reflects the aforementioned benefits of this experimental SAH-model. Considering vasospasm severity, expectedly, severe vasospasm was seen more often on day 5 (49%) compared to day 2 (21%).…”
Section: Cerebral Vasospasm In Experimental Sah Modelssupporting
confidence: 79%
“…Regarding WFNS scoring and Fisher grading, the patients were examined as a dichotomy between low-grade and high-grade SAH presentation-WFNS grades 1 to 3 are considered low grade and 4 and 5 considered high grade; Fisher grades 1 and 2 as low grade and 3 and 4 as high grade. 6,7 All patients admitted to the hospital with nontraumatic SAH were treated with calcium channel blockade in the form of nimodipine.…”
Section: Methodsmentioning
confidence: 99%
“…The sham group underwent identical procedures without the vascular perforation. The severity of SAH was blindly assessed at the time of sacrifice according to the previously described grading system [13]. Rats displaying SAH severity scores between 8-13 were used for further experiments [14].…”
Section: Sah Model Conducted By Means Of Endovascular Perforationmentioning
confidence: 99%